Environmental odor detection and classification with electronic nose system - Macías-Quijas, Ricardo; Velázquez, Ramiro; Del-Valle-Soto, Carolina; Lizut, Rafal; Visconti, Paolo; Lay-Ekuakille, Aimé (Institute of Advanced Engineering and Science, 2025)
A prototype of an electronic nose (e-nose) system integrating a set of general-purpose gas sensors, an electronic module, and signal processing and classification methods has been designed and implemented to detect certain environmental odors that might pose a risk to human health. The proposed device explores the filter diagonalization method (FDM), an advanced signal processing technique for accurate spectral estimation, to detect the presence of odors together with random forest (RF), a popular machine learning algorithm, to classify the features of such spectra. Experimental results show that the proposed FDM-RF approach can recognize the targeted odors with an accuracy of 96.4%.